Respuesta :

Since they’re both in standard form and they both say that y is equal to something, you just have to set them up with one another
2x-10=4x-8
Subtract 2x
-10=2x-8
Add 8
-2=2x
Divide by 2
-1=x
x=-1
Check it by inserting it
2(-1)-10=4(-1)-8
-2-10=-4-8
-12=-12
So x=-1 is the answer

Answer:

-1

Step-by-step explanation:

Move all terms containing  x

to the left side of the equation.

Tap for fewer steps...

Subtract  4x from both sides of the equation.

2 x−10−4x= −8 y=4x−8

Subtract  4 x  from  2 x − 2 x− 10= − 8 y = 4 x − 8

Move all terms not containing  x  to the right side of the equation.

Tap for more steps...

− 2 x = 2 y = 4 x − 8

Divide each term by  − 2  and simplify.

Tap for fewer steps...

Divide each term in  − 2 x= 2  by  − 2 .

− 2 x − 2 = 2 − 2 y = 4 x − 8

Simplify the left side of the equation by cancelling the common factors.

Tap for fewer steps...

Reduce the expression by cancelling the common factors.

Tap for more steps...

− ( − 1 ⋅ x ) = 2 2 y = 4 x − 8

Rewrite  

− 1 ⋅ x  as  - x . x = 2 − 2 y = 4 x − 8

Divide  2  by  − 2 .

x = − 1 y = 4 x − 8

Replace all occurrences of  x  with the solution found by solving the last equation for  x . In this case, the value substituted is  − 1 . x= − 1 y = 4 ( − 1 ) − 8

Simplify  4 ( − 1 ) − 8 .

Tap for fewer steps...

Multiply  4 by  − 1 .

x = − 1 y = − 4 − 8

Subtract  8  from  - 4 .

x = − 1 y = − 12

The solution to the system of equations can be represented as a point.

( − 1 , − 12 )

The result can be shown in multiple forms.

Point Form:  ( − 1 , − 12 )

Equation Form:  x  =− 1  ,y = − 12

ACCESS MORE